Phenotypic Multiorgan Involvement of Subclinical Disease as Quantified by Magnetic Resonance Imaging in Subjects With Prediabetes, Diabetes, and Normal Glucose Tolerance. Issue 6 (June 2018) - Storz, Corinna; Rospleszcz, Susanne; Lorbeer, Roberto; Hetterich, Holger; Auweter, Sigrid D.; Sommer, Wieland; Machann, Jürgen; Gatidis, Sergios; Rathmann, Wolfgang; Heier, Margit; Linkohr, Birgit; Meisinger, Christa; et al.
Abstract : Introduction: Detailed mechanisms in the pathophysiology of diabetes disease are poorly understood, but structural alterations in various organ systems incur an elevated risk for cardiovascular events and adverse outcome. The aim of this study was to compare multiorgan subclinical disease phenotypes by magnetic resonance (MR) imaging to study differences between subjects with prediabetes, diabetes, and normal controls. Materials and Methods: Subjects without prior cardiovascular disease were enrolled in a prospective case-control study and underwent multiorgan MR for the assessment of metabolic and arteriosclerotic alterations, including age-related white matter changes, hepatic proton density fat fraction, visceral adipose tissue volume, left ventricular remodeling index, carotid plaque, and late gadolinium enhancement. Magnetic resonance features were summarized in a phenotypic-based score (range, 0–6). Univariate, multivariate correlation, and unsupervised clustering were performed. Results: Among 243 subjects with complete multiorgan MR data sets included in the analysis (55.6 ± 8.9 years, 62% males), 48 were classified as subjects with prediabetes and 38 as subjects with diabetes. The MR phenotypic score was significantly higher in subjects with prediabetes and diabetes as compared with controls (mean score, 3.00 ± 1.04 and 2.69 ± 0.98 vs 1.22 ± 0.98, P < 0.001 respectively), also after adjustment for potential confounders. We identified 2 clusters of MR phenotype patterns associated with glycemic status ( P < 0.001), independent of the MR score (cluster II–metabolic specific: odds ratio, 2.49; 95% CI, 1.00–6.17; P = 0.049). Discussion: Subjects with prediabetes and diabetes have a significantly higher phenotypic-based score with a distinctive multiorgan phenotypic pattern, which may enable improved disease characterization. Abstract : Supplemental digital content is available in the text.